2015
DOI: 10.1080/05704928.2015.1118637
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of explosives by surface enhanced Raman scattering

Abstract: Surface Enhanced Raman Scattering (SERS) has undergone an important development over the last few years, particularly in the detection and identification of extremely low traces of explosives. The large number of studies and results generated by this increasing research makes a comprehensive overview necessary. This work reviews in detail that research focused on the identification of explosives by SERS, including TNT, DNT, RDX, PETN, TATP, HMTD, perchlorate, etc. either in bulk state, in solution or in vapour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 89 publications
(308 reference statements)
1
29
0
Order By: Relevance
“…In addition, TNT is also widely used in underwater explosion and many other industrial applications, which could lead to the contamination of soil and ground water (Yang et al, 2010). A variety of technologies such as mass spectroscopy, photoluminescence (PL), chromatography and Raman spectroscopy (GrahamáCooks, 2005; Harvey et al, 1990; He et al, 2015; Zhen et al, 2016) are currently employed to detect TNT in the environment, among which surface-enhanced Raman scattering (SERS) is one of the most popular detection techniques (Dasary et al, 2009; Hamad et al, 2014; Jamil et al, 2015a, 2015b; Zapata et al, 2016). Although ultra-high detection sensitivity has been reported, surface functionalization of the SERS substrates sometimes are required and the Raman signals actually come from the probe molecules rather than TNT itself (Hakonen et al, 2015; He et al, 2015; Yang et al, 2010) because the binding affinity of TNT toward metallic nanoparticle surfaces is very low.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TNT is also widely used in underwater explosion and many other industrial applications, which could lead to the contamination of soil and ground water (Yang et al, 2010). A variety of technologies such as mass spectroscopy, photoluminescence (PL), chromatography and Raman spectroscopy (GrahamáCooks, 2005; Harvey et al, 1990; He et al, 2015; Zhen et al, 2016) are currently employed to detect TNT in the environment, among which surface-enhanced Raman scattering (SERS) is one of the most popular detection techniques (Dasary et al, 2009; Hamad et al, 2014; Jamil et al, 2015a, 2015b; Zapata et al, 2016). Although ultra-high detection sensitivity has been reported, surface functionalization of the SERS substrates sometimes are required and the Raman signals actually come from the probe molecules rather than TNT itself (Hakonen et al, 2015; He et al, 2015; Yang et al, 2010) because the binding affinity of TNT toward metallic nanoparticle surfaces is very low.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review, the recognition of explosives in different states was summarized, the potential of SERS for vapor detection of explosives through SERS sensors as chemical noses was shown, and the problems of perchlorate anion detection in water was reviewed [121]. Hakonen et al discussed the possible use of SERS for convenient in-situ threat recognition and summed up existing SERS detection methods and substrates with a distinctive focus on ultra-sensitive real-time detection [122].…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…There has been a lot of research in the area of detecting explosive components/by-products [92,93], however, there is limited literature involving OAD derived SERS in this area [31]. The work done by Nuntawong et al have shown the use of oblique magnetron sputtering deposition, which in itself is rare.…”
Section: Explosive Components Detectionmentioning
confidence: 99%